The status of prosody and its role in establishing Linguistics - belgat, khalil (The Notebooks of the Algerian Poetics Laboratory Journal, 2025)
This intervention aims to highlight the fundamental value that prosody acquires in revealing some phonetic and linguistic features and extrapolating them in the field of Arabic poetry. Prosody is a genius science that stands on its own. It is what faithfully preserved the poetic narrative and thus compensated for the audio narrative lost before the time of composition and recording means. It is The scale by which poetry is presented with its linguistic, phonetic, and lexical templates, and by which true poetry is known from poor poetry, thus we cannot separate it from the science that regulates its rules, which is the science of prosody. The results that this study seeks are to highlight the important role of prosody in deconstructing the poetic language into fixed linguistic and phonetic provisions. Poetry is the collection of the Arabs, so there must be an officer who preserves this narration in a reliable manner, and then deconstructs this structure into fixed linguistic data. Therefore, there was a need Linguists are desperate for the science of prosody, and they pass down poetry from generation to generation.